REVIEW OF SHARIA ECONOMIC LAW REGARDING THE ELECTRIC VEHICLE TAX RELIEF POLICY - Lafiana Hikmawati; Mahfud (Adisam Publisher, 2024)
The government has implemented a number of policies that support the development and increasing demand for electric vehicles. One way is by reducing taxes on electric vehicles, both two-wheeled and four-wheeled electric vehicles. Based on this, this research aims to analyze the electric vehicle tax relief policy from a sharia economic perspective, especially regarding maqashdi sharia. This research is qualitative research with a descriptive approach, namely describing the views of sharia economic law regarding tax relief for electric vehicles. The data used in this research is secondary data that researchers obtained from a number of credible sources which are commonly used in every scientific research including books, national and international indexed scientific articles, trusted websites, and various other sources. These data were analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions. The result in this research show 1. The government is implementing a tax reduction policy for electric vehicles with the aim of reducing emissions and protecting the environment. The goal is for people to switch to electric vehicles. 2. There are 5 objectives of sharia law, including the objectives of sharia economics, namely Al- Kulliyat Al-Khamsah, namely protecting religion, protecting offspring, protecting property, protecting the mind, and protecting the soul. As the thinking of the fuqoha', KH Ali Syafe'i, proposed a new goal, namely protecting the environment. 3. The government's policy to reduce taxes on electric vehicles is in line with Al- Kulliyat Al-Khamsah and protecting the environment proposed by KH Ali Syafe'i.